ANALISIS NILAI HAMBATAN TOTAL DENGAN PERUBAHAN SARAT KAPAL KM. KENDHAGA NUSANTARA 6 - Utomo, Budi; Sulaiman, Sulaiman (Gema Teknologi, 2020)
The calculation of total resistance value is important of ship becauseÂ  affects the speed of fluid flow that occurs, as well as the speed of the ship.So that in the designing new ships, sea trials are needed to find out whatever the preparedness of the ship is planned. The purpose is to obtain the value of the total resistance and the coefficient of ship resistance KM. Kendhaga Nusantara 6 uses the calculation method for each ship draught/loading condition. The Method used is experimental method with numerical value approach, Denny Mumford theory and Froude's number. The results show that the largest Total Resistance (Rt) is 5646,02 kN, it was found when speed of ship was 12 knots and draught ship 3,5 meters, with a coefficient value (Ct) of 7,757 x 10-3. The difference in value (Ct) is 0,032x10-3 or 0.41%, and it is still in the criteria because it is below 5%.